Determinants of Mobile Banking Use at SUMUT Bank Customer Sharia Branch - Maarif, Muhammad Ariful; kurnia, rahmat; farizal, nando; hidayati, ayu (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Mobile banking is a bank service that allows customers to transact easily using the available internet network. However, the convenience of this service has not been fully utilized by customers of the Padangsidimpuan Syariah Branch of Bank Sumut. This study aims to determine whether there is an influence of information technology, service features, and convenience on the interest in using Mobile banking partially and simultaneously. The discussion in this study is related to customer interest in using Mobile banking in the field of banking science. The approach taken is theories related to interest in using Mobile banking. This research is a quantitative study using primary data obtained from distributing questionnaires. The population in this study are customers of Bank Sumut Syariah in 2020. Sampling used the Taro Yamane formula so that 99 customers were obtained as respondents.Keywords: Mobile banking, Determine, Shariah Branch.